The Influence of the Success of the Surabaya Citizens' Love Application using TAM and Delone Mclean - pradana, brillyan putra; Wulansari, Anita; Safitri, Eristya Maya (Sistemasi: Jurnal Sistem Informasi, 2024)
The Surabaya City Government launched an application based on an internet site or web page in the form of a data collection system carried out by the local Kader Surabaya Hebat (KSH) to record various problems in the community related to poverty and health problems, the application was named the Sayang Warga Application (ASW). The application that was launched does not mean it has shortcomings because until now the application has never been maintained, causing ASW to be considered less than optimal and this clearly hinders the performance of users in conducting data collection. This study uses the right method to achieve a goal. From what can be traced and studied, the appropriate method is to use a quantitative method. This study uses the Partial Least Square-Structural Equation Model (PLS SEM) method. The results of 12 variable relationship paths, 4 variable path relationships were declared insignificant and rejected because the T-test and P-value values were below 1.96 and 0.05, while 8 variable path relationships were declared significant and accepted because the T-test and P-Value values were above the threshold, namely 1.96 and 0.05. Furthermore, the results of the analysis of factors that influence the success of use in ASW can be concluded, the results of the hypothesis test indicate that perceived ease of use has a positive and significant effect on perceived usefulness. Because the hypothesis path has the highest value with a T-test of 6,560 with a P-Value of 0.000